Adubação silicatada e sua influência nos atributos químicos do solo e nutrição do trigo - Sarto, Marcos Vinicius Mansano (2014)
The application of calcium silicate and magnesium can promote improvements in soil chemical properties and, consequently, improve nutrition and increase crop productivity. Thus the present study aimed to evaluate the effect of doses of calcium silicate and magnesium on soil chemical properties, development and nutrient uptake by wheat in soils of the state of Paraná. The experiment was conducted in a greenhouse in pots with three soil types in the state of Paraná. The experimental design was randomized blocks, factorial 5 x 3, with four replications. Treatments consisted of application of 0, 1, 2, 4 and 6 Mg ha-1 of calcium silicate and three soils: Red Latosol eutrophic (LVef), Red Yellow Argissoil eutrophic (PVAe) and Red Latosol distroferric (LVd). Silicon fertilization increased the contents of Si, Ca and Mg and pH, CTC and V reduced the potential acidity (H+Al) and Al content of the soil. Silicon fertilization did not influence the agronomic traits of wheat grown in soils LVef and PVAe, however, soil LVd increased the dry matter of shoots, plant height, number of tillers and yield of wheat crop. The amount of Si accumulated by the shoots of wheat from the silicate applied ranged from 28.2 %, 60.61 % and 74.14 %, respectively, for the LVef, PVAe and LVd soils. Silicon fertilization promotes increase of K, Ca and Mg and reduces the levels of Zn and Mn in the leaves of wheat. Monitoring with DRIS possible to detect the effect of doses of calcium silicate and magnesium in soil nutrient balance in the leaf tissue of wheat